Optimizing Maritime Industry Management: An Innovative Leak Repair Technique for Ballast and Cargo Tanks - Wijaya, Haryadi (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2024)
The operation of ships at sea involves various risks, including damage to the ship's structure, particularly to the ballast tanks and cargo tanks. Leaks in these tanks can cause significant financial losses, seriously impact the environment, and even threaten lives at sea. Therefore, this study aims to analyze the causes of leaks in ballast tanks and implement repair techniques used to address leaks in the ballast and cargo tanks on the vessel MT. Sepinggan. It also evaluates maintenance practices that include technical patching procedures and regular docking as part of ship management strategies. This research uses field research methods and literature studies with a qualitative descriptive approach, where the research sample is taken through purposive sampling with MT Sepinggan as the research object. The study shows leaks in the ballast tanks of MT. Sepinggan is caused by delayed docking and a lack of routine maintenance, which makes the tank plates thin and prone to leakage. Repair techniques, including patching procedures and regular docking schedules, have proven effective in addressing leaks and improving ship management. Limited funds and uncertainty of ship operational routes also resulted in irregular maintenance schedules.